Entrepreneurship and Innovation in Obtaining Competitive Advantage in Non-Formal English Education Industry in Indonesia: A Model Proposition - Respati Wulandari (Bina Nusantara University, 2021)
This study aims to examine the effect of entrepreneurship on innovation in the non-formal English education industry geared towards achieving competitive advantage. Entrepreneurship is viewed through leadership, culture and entrepreneurship. Entrepreneurial leadership is a leadership approach that involves managerial and entrepreneurial capacity where this type of leadership is effective in running the business. So far, research on non-formal education in English through an entrepreneurial perspective and a strategic entrepreneur approach is very limited. Thus, a model proposal is constructed derived and drawn from the qualitative research that was conducted. This study will provide a review of entrepreneurship and innovation in non-formal education businesses in English.